Understanding banking sector globalization - Goldberg, Linda S. (2009)
Highlights the recent evolution and consequences of banking sector globalization. Presents an overview of the macroeconomic consequences of banking sector globalization, including the role of banks in the international transmission of shocks, movements of business cycles, financial crises and economic growth. Argues that banking globalization can have important consequences for financial supervision and regulation.